Detection of new mutations and molecular pathology of mild and moderate haemophilia A patients from southern Brazil. (28th May 2013) - Rosset, C.; Vieira, I. A.; Sinigaglia, M.; Gorziza, R. P.; Salzano, F. M.; Bandinelli, E.
Summary: A total of 76 unrelated male patients with mild ( n  = 55) or moderate ( n  = 21) haemophilia A living in the southern Brazilian state of Rio Grande do Sul were studied by direct sequencing of all F8 26 exons, the 5′ UTR and 3′ UTR, intron–exon junctions and the promoter region. When no mutation was found, a multiplex ligation‐dependent probe amplification analysis was performed. We identified the disease‐causing mutations in 69 patients, who showed 33 different mutations: 27 missense, one small deletion, two small duplications and three splice site mutations. Seven missense and two splice site mutations were not previously reported in HAMSTeRS and were not identified in any current literature search. Nine recurrent mutations were found, one of them never described before (p.Tyr1786Phe). Haplotype analysis indicated that this mutation had originated in the Brazilian population as a single event in a common ancestor. The possible influence of these mutations in the determination of the disease was carefully considered, including bioinformatic tools. These data add to the general knowledge of the disease and can also be useful for HA diagnosis and detection of carriers in the southern Brazilian population.